2018
DOI: 10.3145/epi.2018.nov.06
|View full text |Cite
|
Sign up to set email alerts
|

Politics, hackers and partisan networking. Misinformation, national utility and free election in the Catalan independence movement

Abstract: Miguel earned a Ph.D. in Sociology from UNED, MBA and an executive master in e-Business from IE Business School (Madrid), as well as a master in Information Society and Knowledge (Universitat Oberta de Catalunya). He is a founding member of casadelibro.com and has worked professionally as the director of marketing and communications for Elsevier Spain and Casa del Libro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…[64], due to political, economic, or strategic interests, with the effect of the manipulation of public opinion. The limits of verisimilitude are blurred, and the messages are sensationalist and more emotional [9] than rational, following the idea that, since "emotions and feelings are real, it's concluded that the objectives are also real and, therefore, shared emotions are important. That is, emotion and feelings are equated with truth and legality" [9].…”
Section: Social Network and Misinformation In The Face Of Natural Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…[64], due to political, economic, or strategic interests, with the effect of the manipulation of public opinion. The limits of verisimilitude are blurred, and the messages are sensationalist and more emotional [9] than rational, following the idea that, since "emotions and feelings are real, it's concluded that the objectives are also real and, therefore, shared emotions are important. That is, emotion and feelings are equated with truth and legality" [9].…”
Section: Social Network and Misinformation In The Face Of Natural Dis...mentioning
confidence: 99%
“…9. ): mis-information, information shared without intent to harm; disinformation, information shared with intent to harm; and misinformation, truthful private information shared to cause harm [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…As already noted, emotion is expressed as a basic physiological reaction that cannot be concealed, so that rationalisation associates its certainty with the authenticity of that which provoked it, and links that sensation to a feeling, a mental experience associated with the vital state that generated it (Damasio, 2018). Sensation becomes an emotional event (Weeks, 2015), an emotional epistemology (Del-Fresno & Manfredi, 2018;Adler & Drieschova, 2021) or the rumour-mongering of self-consumption (Rojecki & Meraz, 2016). The right to feel different, ignored, aggrieved or appreciated can lead to a demand for political rights grounded in difference.…”
Section: Disinformation Is a Political Activitymentioning
confidence: 99%
“…34 Del Fresno and Manfredi (2018) analysed the content produced by Julian Assange and WikiLeaks in support of the independence process in the period 25 September to 15 November, finding that Assange adhered 'to the narrative and pro-independence worldview, equating it with all of Catalonia and ignoring the existence of the other half of society, which is also Catalan and not pro-independent' and that constructed 'the perception of Spain as a dictatorship or non-democratic state' . 35 Amplification through bots and fake accounts On 27 March 2018, an article on 'How Twitter Bots Help Fuel Political Feuds' published in the Scientific American referenced the joint research conducted by researchers at Fondazione Bruno Kessler in Italy and at the University of Southern California, on the use of social bots related to the Catalonian referendum. The authors identified two polarized factions of Twitter users as Independentist and Constitutionalist and quantified 'the structural and emotional roles played by social bots' .…”
Section: Allegations Of External Meddlingmentioning
confidence: 99%